Secret of Gujarat's agrarian miracle after 2000 - Shah, Tushaar; Gulati, A.; Hemant, P.; Shreedhar, G.; Jain, R.C. (2009)
Semi-arid Gujarat has clocked high and steady growth at 9.6% per year in agricultural state domestic product since 1999-2000. What has driven this growth? The Gujarat government has aggressively pursued an innovative agriculture development programme by liberalising markets, inviting private capital, reinventing agricultural extension, improving roads and other infrastructure. Canal-irrigated South and Central Gujarat should have led Gujarat's agricultural rally. Instead it is dry Saurashtra and Kachchh, and North Gujarat that have been at the forefront. These could not have performed so well but for the improved availability of groundwater for irrigation. Arguably, mass-based water harvesting and farm power reforms have helped energise Gujarat's agriculture.